Pendekatan AHP dan Fuzzy AHP pada Keputusan Pemilihan Pembeli Biji Jagung Hasil Pertanian - Alman Rizky Mulianta Ginting; Yosef Daryanto; Ririn Diar Astanti (Universitas Islam Raden Rahmat, Malang, 2024)
Generally, post-harvest handling of corn production involves collecting agents who shell whole corn into kernels before selling them to processing companies. Due to fairly rapid price changes and different criteria for each company, corn seed purchasing companies are selected to maximize agent profits. This research aims to help corn seed collecting agents (sellers) prioritize sales to several processing companies (buyers). A case study was conducted on the production of corn grain in Tiga Binanga District which was sold to processing companies in Medan, North Sumatra. Buyer priority decisions are made using the Analytical Hierarchy Process (AHP) and Fuzzy AHP (FAHP) methods. The results obtained from both methods have the same priority ranking for 1-3 (buyers M, G, I) but differ for the ranking 4-6. The buyers' priority for the last 3 rankings is C, L, S or L, C, S. Therefore, for buyer selection decisions, agents can utilize the priority ranking and apply this method for any changes that may occur.